2017
DOI: 10.3390/plants6020023
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Role of the ECERIFERUM2-LIKE Clade of the BAHD Acyltransferase Superfamily in Cuticular Wax Metabolism

Abstract: The elongation of very-long-chain fatty acids is a conserved process used for the production of many metabolites, including plant cuticular waxes. The elongation of precursors of the most abundant cuticular wax components of some plants, however, is unique in requiring ECERIFERUM2-LIKE (CER2-LIKE) proteins. CER2-LIKEs are a clade within the BAHD superfamily of acyltransferases. They are known to be required for cuticular wax production in both Arabidopsis and maize based on mutant studies. Heterologous express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 69 publications
0
32
1
Order By: Relevance
“…Based on Arabidopsis ksc mutant analyses, the KCS enzyme KCS6/CER6 was found to be central for cuticular wax biosynthesis, as it elongates C 24 to C 28 acyl-CoAs. More recently, it was shown that the KCS6/CER6 FAE complex may be associated with CER2-LIKE proteins, then enabling elongation of acyl-CoAs up to C 34 ( Figure 3 ), yet the mechanism of action of CER2-LIKE proteins remains unknown [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Arabidopsis ksc mutant analyses, the KCS enzyme KCS6/CER6 was found to be central for cuticular wax biosynthesis, as it elongates C 24 to C 28 acyl-CoAs. More recently, it was shown that the KCS6/CER6 FAE complex may be associated with CER2-LIKE proteins, then enabling elongation of acyl-CoAs up to C 34 ( Figure 3 ), yet the mechanism of action of CER2-LIKE proteins remains unknown [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…5B and 7). The frond epidermal cells were defined by the marker gene ECERIFERUM-like , which has been shown to be important for cuticle wax development (Haslam et al, 2017). Additional markers include an auxin efflux carrier in starch metabolising cells PIN-FORMED (PIN7) aiding root termination (Kim et al, 2013; Rosquete and Kleine-Vehn, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Two important facets must be kept in mind when contemplating this question. Firstly, the ubiquitous KCS elongation systems require At CER-22-like proteins for the final elongation steps [ 57 ]. When these genes are mutated, shorter chain lengths are present in the wax.…”
Section: Discussionmentioning
confidence: 99%
“… What genes determine the deduced thioesterase, decarboxylase, methylketone reductase, and ester synthase enzymes in the alkan-2-ol ester branch pathway? Why are AtCER2 orthologs, that are required for the final KCS elongation steps of ubiquitous wax aliphatics [ 57 ], apparently not required for the final elongations in synthesis of the β-diketone aliphatics? What are the roles of the barley Cer-a , - b , - x and - yl loci products in eliminating almost all or all synthesis of polyketide wax aliphatics, and simultaneously modifying synthesis of ubiquitous wax aliphatics?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation